2017
DOI: 10.1111/1346-8138.13833
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of positron emission tomography imaging to detect lymph node metastases in patients with extramammary Paget's disease

Abstract: Patients with extramammary Paget's disease (EMPD) have a relatively good prognosis, when spread of the tumor cells is limited to the epidermis. However, invasive EMPD has a poor prognosis, when the patients have regional lymph node metastasis. Detection of nodal metastasis is thus mandatory to manage EMPD. To evaluate the F-fluorodeoxyglucose positron emission tomography (FDG-PET) imaging to assess lymph node metastasis, 15 patients with histologically proven primary EMPD were enrolled in this study. All patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…In the present study, PET/CT was performed immediately prior to surgery for each of the patients and showed a high association with the final pathology. Previous studies have revealed that regardless of LN swelling, the SUVmax of LN-positive cases is significantly higher compared with that of LN-negative cases (22). A study of 33 patients showed that the sensitivity and specificity of PET/CT in detecting metastatic LNs were 75.0 and 96.4%, respectively (23).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the present study, PET/CT was performed immediately prior to surgery for each of the patients and showed a high association with the final pathology. Previous studies have revealed that regardless of LN swelling, the SUVmax of LN-positive cases is significantly higher compared with that of LN-negative cases (22). A study of 33 patients showed that the sensitivity and specificity of PET/CT in detecting metastatic LNs were 75.0 and 96.4%, respectively (23).…”
Section: Discussionmentioning
confidence: 92%
“…There have been several case reports on the use of PET/CT in LN-metastatic EMPD cases. These previous studies have revealed that the maximum standardized uptake value (SUVmax) may be useful for detecting nodal metastasis in EMPD cases (3,57).…”
Section: Introductionmentioning
confidence: 99%
“…FDG‐avidity can also help detect true nodal metastasis. Fujiwara and colleagues examined the relationship between SUV max values and lymph node metastasis . They found that SUV max is potentially useful to when evaluating the need for sentinel lymph node biopsy (SLNB) in EMPD.…”
Section: Resultsmentioning
confidence: 99%
“…Positron emission tomography images have been reported to be effective for detecting LNM in patients with EMPD. 22 On the other hand, for early EMPD management with no clinical evidence of nodal metastases, some authors have suggested the use of sentinel lymph node (SLN) biopsy. [10][11][12] This suggests that a significant proportion of patients with no initial clinical evidence of nodal metastases may harbor clinically silent micrometastases, and confirmation of lymph node disease by SLN biopsy or imaging can help determine treatment strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Enlargement of regional nodes is caused by previous or concurrent infections and inflammation, leading to reactive lymphadenopathy; thus, accurate clinical diagnosis is difficult. Positron emission tomography images have been reported to be effective for detecting LNM in patients with EMPD . On the other hand, for early EMPD management with no clinical evidence of nodal metastases, some authors have suggested the use of sentinel lymph node (SLN) biopsy .…”
Section: Discussionmentioning
confidence: 99%